COMMUNICATION STRATEGY OF THE GENERAL ELECTION COMMISSION TO INCREASE COMMUNITY PARTICIPATION IN USING THE RIGHT TO VOTE IN THE 2019 ELECTION IN NGANJUK DISTRICT - Rahmawati, Misna Muzdalifa; Munir, Ahmad (QAULAN: Journal of Islamic Communication, 2022)
Abstract: The purpose of this study is to describe the Communication Strategy of the General Elections Commission (KPU), to analyze the factors that influence public participation and to identify the barriers to increasing public participation. The researcher used a qualitative research approach, with data collection procedures using observation, in-depth interviews, and documentation. The data analysis used is the Miles and Huberman model data analysis technique which is carried out interactively and also takes place continuously including: data reduction, data presentation, conclusion drawing and verification. The results of this study are the strategies used by the Nganjuk KPU in increasing community participation by conducting face-to-face activities directly, carrying out activities that attract public attention, providing information through various media, using democratic volunteers to invite various segments of society. Factors that influence the increase in community participation are public awareness of elections, voter socialization and education, the role of election participants and finally the role of local governments and stakeholders. Then the obstacles to improving the community are administrative constraints, time, lack of human resources in the internet segment, election day elections, lack of coordination between KPU officers and KPPS.